MODEL PERENCANAAN KANVAS PROGRAM SOSIAL PADA PUSAT PELAYANAN SOSIAL KARYA WANITA (PPSKW) MATTIRO DECENG KOTA MAKASSAR PROVINSI SULAWESI SELATAN - Fasa, Zaky Miftahulfasa (Jurnal Ilmu Pekerjaan Sosial, 2023)
Social welfare is an interesting topic to discuss, because it is a cross-sectional issue related to many things. One of the government's efforts to realize social welfare mandated in Act Number 11 of 2009 is to provide guidance and services in orphanages in accordance with Government Regulation Number 2 of 2018, concerning minimum service standards. The Women's Social Service Center (PPSKW) Mattirodeceng is one of the technical implementing units at the South Sulawesi Province Social Service which provides social services for prostitutes who violate Regional Regulation Number 2 of 2021 concerning the administration of public order and peace and public protection and is referred to by the Social Service Regencies/Cities in South Sulawesi. The needs assessment shows that the evaluation of service implementation focuses on planning that has not been maximized. The purpose of this study is to provide an overview of the Social Program Canvas Planning Model as an alternative to the planning model for government-owned institutions. This research uses action research with a qualitative approach that starts with an assessment of the needs of the Human Services Organization (HSO) management, preparation of a draft model, implementation of a draft model, evaluation of the results of model implementation, and a final model. Collection and processing of data using interviews/interviews, observation, and focus group discussions. The data validity technique uses credibility, transferability, dependability and confirmability tests. Data analysis used is data reduction, data presentation and conclusion. The results of this study describe the Social Program Canvas Planning Model used by the discussion method between all elements of the institution. The points that become concepts/ideas/ Ideas/suggestions are written in metacards/sticky notes and pasted on the canvas. The implications of this model improve the quality of planning and the quality of social services at UPT PPSKW Mattiro Deceng.